Peningkatan Kepuasan Kerja Melalui Lingkungan Kerja Karyawan CV Artha Mandiri Group Kabupaten Merangin - Reni Devita; Rasdi Rasdi; Khuluqon Azima (Eksis: Jurnal Ilmiah Ekonomi dan Bisnis, 2023)
CV Artha Mandiri Group is a company (Persero) engaged in equipment leasing and contracting. This study aims to describe job satisfaction, work environment, CV Artha Mandiri Group Merangin Regency, to find out and analyze the increase in job satisfaction and work environment.  To answer the research objectives, the authors used theoretical studies related to research variables, namely job satisfaction, work environment. In addition, the authors also look for relevant previous research in the form of previous articles/journals and theses to support this research. This research uses quantitative methods. The population in this study were employees of CV Artha Mandiri GroupThe results of a simple linear regression analysis are obtained by the equation Y = 1.773 +0.032 Meanwhile, from the hypothesis testing carried out. The results obtained show that job satisfaction and work environment have increased significantly Merangin Regency, totaling 98 employees. Based on the results of data analysis and discussion in this study, it can be it can be concluded that CV Artha Mandiri Group Merangin Regency has high job satisfaction, unfavorable work environment. For this reason, it is hoped that in the future we can focus more on improving a more conducive work environment so that employee performance is higher than before.